The Influence Of Scramble Learning Model On Interest In Learning Of Social Science To Fourth Grade Students Of Public Elementary Schools In Pejagoan Subdistrict Kebumen Regency In Academic Year 2019/2020 - Rahmayanti, Lutfiana; Joharman, Joharman; Salimi, Moh (Universitas Sebelas Maret, 2021)
The study aimed to determine the interest in learning on social science before and after having scramble learning model to fourth grade students of public elementary schools in Pejagoan Subdistrict Kebumen Regency in academic year of 2019/2020.The research was a pre-experimental quantitative design in the form of one-group pretest-posttest design.The results indicated that the Sig.(2-tailed) in the hypothesis test was 0,000< 0,05. The result of tcount>ttable was 4,350 > 2,010. In addition, based on the average score of interest in learning of social science, the pretest was 150.00310 and the posttest was 155.52406. It meant that the application of the Scramble learning model effected in increasing students' interest in learning in social science.It concludes that there is difference between the interest in learning on social science before and after having scramble learning model to fourth grade students of public elementary schools in PejagoanSubdistrictKebumen Regency in academic year of 2019/2020